2020
DOI: 10.1007/s42729-020-00346-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Foliar Fertilization: a Review of Current Status and Future Perspectives

Abstract: The use of large amounts of chemical fertilizers promotes high-yield agriculture, but is also associated with a number of problems, such as low fertilizer utilization rates, soil acidification, and soil salinization. Comprehensive studies have shown that spraying chelated fertilizer on leaves can reduce the total amounts of fertilizer applied and achieve high fertilizer efficiency. Foliar fertilizer application after soil fertilization is an effective method to increase the contents of trace elements in crops … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
2
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(102 citation statements)
references
References 135 publications
(94 reference statements)
0
91
2
9
Order By: Relevance
“…It has been observed, for example, that hydroponic cultures can be among the best options to increase the nutrient content of plant tissues [ 39 , 40 ]. In the case of minerals not readily translocated to the edible tissues, such as for crops grown on soil and/or for minerals with scarce mobility, another alternative is the use of foliar fertilization [ 41 ].…”
Section: Agronomic Mineral Biofortificationmentioning
confidence: 99%
“…It has been observed, for example, that hydroponic cultures can be among the best options to increase the nutrient content of plant tissues [ 39 , 40 ]. In the case of minerals not readily translocated to the edible tissues, such as for crops grown on soil and/or for minerals with scarce mobility, another alternative is the use of foliar fertilization [ 41 ].…”
Section: Agronomic Mineral Biofortificationmentioning
confidence: 99%
“…Yang et al (2014;Ding et al, 2015) performed a comparative analysis between sorbitol alcohol and sorbitol calcium fertilizer and which concluded that both promote the absorption of nutrients by crops. However, the chelation reaction between sorbitol and inorganic salt has not been characterized, nor has there been any comparative analysis of the fertilizing effect of sorbitol chelated and sorbitol non-chelated minerals (He et al, 2019;Niu et al, 2020). The mechanism of action of sorbitol alcohol or sorbitol alcohol chelation on crops is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Treating plants with 8 or 10 mg/L Se slightly, but significantly reduced net assimilation rate of CO 2 (A N , Figure 4 A), stomatal conductance to water vapour (g SW , Figure 4 B) and ratio of intercellular to atmospheric CO 2 concentration (C i /C a, Figure 4 C), which indicates that higher selenium concentrations enhanced stomatal limitation of photosynthetic CO 2 assimilation in Stevia plants, but 6 mg/L Se treatments did not show significant effect on CO 2 assimilation and related parameters. Although the effect of exogenous Se on photosynthesis has been examined in several plant species [ 73 , 79 ], to the best of our knowledge, there is no information available in the literature about the impact of Se supplementation on the photosynthetic activity of Stevia plants. Selenium supplementation mostly enhances or does not influence photosynthesis depending on the examined plant species [ 73 ].…”
Section: Resultsmentioning
confidence: 99%